Clinical variations and therapy of patients with rosacea - L. A. Yusupovа; E. I. Yunusovа; Z. Sh. Garaeva; G. I. Mavlyutova; E. M. Valeeva (Лечащий Врач)
The article presents data on rosacea, a widespread inflammatory dermatosis characterized by skin lesions, affecting mainly the skin of the face. The article reveals the pathogenic mechanisms, unfavorable trigger risk factors of the disease, features of the clinic, management and methods of treatment of patients with rosacea.